Antipsychotics and Venous Thromboembolism Risk: A Meta-Analysis - Zhang, R.; Dong, L.; Shao, F.; Tan, X.; Ying, K. (Pharmacopsychiatry, 2011)
Antipsychotics have been inconclusively implicated in susceptibility to venous thromboembolism (VTE).The aim of this study was to investigate the association between antipsychotic drugs and VTE risk by a meta-analysis. PubMed and EmBASE databases were searched for publications through to 10 October 2010. Statistical analysis was performed using Revman 4.2 and Stata 10.0 software.7 case-control studies involving 31 095 cases and 143 472 controls were analyzed. The results indicate that antipsychotic exposure confers a 139% increased risk of VTE (odds ratio [OR]=2.39, 95% confidence interval [CI]:1.71–3.35). Pooled estimates by drug type showed that use of low-potency antipsychotics (OR=2.91, 95% CI 1.80–4.71) is the most important risk factor for VTE, followed by atypical (OR=2.20, 95% CI 1.22–3.96), conventional (OR=1.72, 95% CI 1.31–2.24) and high-potency drugs (OR=1.58, 95% CI 1.50–1.67).This meta-analysis suggests that antipsychotics are a risk factor for VTE. Additional studies in large cohorts are required to validate our findings. Future analyses should study potential effect modifications by different doses and durations of antipsychotic exposure in different populations.
Keywords: antipsychotics; venous thromboembolism; risk factor; meta-analysis